CONSOLIDATION OF CASTLE GATES: CASE STUDY OF SEFERİHİSAR SIĞACIK CASTLE GATES - Özlem ATALAN (Fırat University, 2019)
Seferihisar is the centrum of the district in the west of Turkey in the Aegean Region within the borders of İzmir City located in the southwest of the settlement. It is bordered by the district of İzmir in the north and east and Aegean Sea in the south and west. Sığacık is a vicinity of the Seferihisar district of İzmir province. İt is 4 km to Seferihisar and 46 km to İzmir. Sığacık is located on the north side of Seferihisar Dilek Peninsula, near the bay of Sığacık. Sığacık Castle, traditional houses, monumental buildings, which remain from 16 th.and 20. th Centuries, constitude the settlement texture of Sıgacık Castle vicinity. Sığacık monumental building texture .are constituted Sığacık Castle and gates, , Sığacık Mosque, a Turkish bath and masjid. From the beginning of early ages, there are samples of original architectural styles coming from the several different cultural impressions which effected Sığacık. Today we can see them in spite of the bad conditions, as the monuments of cultural inheritance. However there is also the element of the destruction of Castle and its gates by external effects inspite of some protective procedures. This article aims to provide solution suggestions by observing and determining which measures should be taken for the Castle and its gates in order to protect and preserve the Sığacık Castle .